2012
DOI: 10.1182/blood-2012-02-410407
|View full text |Cite
|
Sign up to set email alerts
|

The folliculin-FNIP1 pathway deleted in human Birt-Hogg-Dubé syndrome is required for murine B-cell development

Abstract: Birt-Hogg-Dubé (BHD) syndrome is an autosomal dominant disorder characterized by cutaneous fibrofolliculomas, pulmonary cysts, and kidney malignancies. Affected individuals carry germ line mutations in folliculin (FLCN), a tumor suppressor gene that becomes biallelically inactivated in kidney tumors by second-hit mutations. Similar to other factors implicated in kidney cancer, FLCN has been shown to modulate activation of mammalian target of rapamycin (mTOR). However, its precise in vivo function is largely un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
74
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(77 citation statements)
references
References 26 publications
2
74
1
Order By: Relevance
“…Our investigation of the hamel allele reinforces the nonredundant roles of FNIP1 in B-cell development (7,8), skeletal muscle composition (9), and cardiac function (6). We reveal that BCL2 overexpression can partially, but not entirely, rescue B-cell development in the absence of FNIP1, and we provide evidence that FNIP1 is an endogenous negative regulator of AMPK.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our investigation of the hamel allele reinforces the nonredundant roles of FNIP1 in B-cell development (7,8), skeletal muscle composition (9), and cardiac function (6). We reveal that BCL2 overexpression can partially, but not entirely, rescue B-cell development in the absence of FNIP1, and we provide evidence that FNIP1 is an endogenous negative regulator of AMPK.…”
Section: Discussionsupporting
confidence: 70%
“…Fnip1 has been reported to play an essential role in B-cell development (7,8). Mouse FNIP1 consists of 1,165 aa and shares 91% amino acid identity with human FNIP1 and 49% identity with mouse FNIP2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In accordance, heightened glycogen levels were also reported in the muscle tissues of muscle-specific Flcn KO mice as compared to the controls. 21,22 A dual role for glycogen…”
Section: The Glycogen Accumulation Conferred By Loss Of Flcn-1 Is Evomentioning
confidence: 99%
“…Previous studies indicated that Fnip1 deficiency completely blocks B-cell development at the large pre-B-cell stage, whereas conventional αβ T cells develop normally (22,28). In this study, we extended our analyses of Fnip1 −/− mice by examining if Fnip1 is important for the development and function of γδ, NK, and iNKT cells and dendritic cells.…”
Section: Resultsmentioning
confidence: 71%